Opium trade, insurgency, and HIV/AIDS in Afghanistan: relationships and regional consequences. - Griffin, Nevada; Khoshnood, Kaveh (Asia-Pacific journal of public health / Asia-Pacific Academic Consortium for Public Health, 2010)
Global health and conflict studies share key linkages that have important research and policy implications but for which data are currently lacking. This analytical review examines the ongoing conflict in Afghanistan, using it as a basis to develop a conceptual framework that integrates security and public health concepts. The analysis draws on recent peer-reviewed and gray literature to assess the interrelationship among 3 variable clusters and their impact on the emergence of the HIV epidemic in Afghanistan. The evidence suggests that there is a complex indirect relationship linking illicit opium trade, the ongoing insurgency, and forced and spontaneous migration to the emergence of an injection drug use-driven HIV epidemic in Afghanistan. These findings demonstrate a clear need for an integrated cross-disciplinary and regional approach to the emerging threat of HIV/AIDS in Afghanistan, to inform more balanced and effective policy making in this and other regions of strategic global import.
Keywords: Afghan Campaign 2001-; Afghanistan; Databases, Bibliographic; Disease Outbreaks; Heroin Dependence; HIV Infections; Humans; Opium; Refugees; Substance Abuse, Intravenous